Dissociation dynamics of noble-gas dimers in intense two-color IR laser fields - Magrakvelidze, Maia; Thumm, Uwe P. E. (My University, 2013)
We numerically model the dissociation dynamics of the noble-gas dimer ions He[subscript 2]+, Ne[subscript 2]+, Ar[subscript 2]+, Kr[subscript 2]+, and Xe[subscript 2]+ in ultrashort pump and probe laser pulses of different wavelengths. Our calculations reveal a distinguished “gap” in the kinetic energy spectra, observed experimentally for the Ar[subscript 2] dimer [ J. Wu et al. Phys. Rev. Lett. 110 033005 (2013)], for all noble-gas dimers for appropriate wavelength combinations. This striking phenomenon can be explained by the dissociation of dimer ions on dipole-coupled Born-Oppenheimer adiabatic potential curves. Comparing pump-probe-pulse-delay-dependent kinetic-energy-release spectra for different noble-gas dimer cations of increasing mass, we discuss increasingly prominent (i) fine-structure effects in and (ii) classical aspects of the nuclear vibrational motion.
Keywords: Noble-gas dimers